Novel Mutation in the DKC1 Gene: Neonatal Hoyeraal-Hreidarsson Syndrome As a Rare Differential Diagnosis in Pontocerebellar Hypoplasia, Primary Microcephaly, and Progressive Bone Marrow Failure - Dehmel, Maria; Brenner, Sebastian; Suttorp, Meinolf; Hahn, Gabriele; Schützle, Heike; Dinger, Jürgen; Di Donato, Nataliya; Mackenroth, Luisa; von der Hagen, Maja (Neuropediatrics, 2016)
Primary microcephaly and severe developmental delay are complex but unspecific signs pointing to various genetic or acquired diseases. A concomitant finding of hematological failure may lead to the differential diagnosis of rare genetic diseases such as chromosome breakage disorders or diseases associated with telomere dysfunction. X-linked Hoyeraal-Hreidarsson syndrome (HHS) is a rare heterogenic disorder characterized by severe neurological impairment and progressive bone marrow failure. The latter represents the main cause of mortality, usually in early childhood. We report on the clinical course of an infant with HHS due to a novel mutation in the DKC1 gene and the particular finding of pontocerebellar hypoplasia.
Keywords: progressive bone marrow failure; primary microcephaly; pontocerebellar hypoplasia; DKC1 gene; Hoyeraal-Hreidarsson syndrome